Body Size Differences between Foraging and Intranidal Workers of the Monomorphic Ant Lasius niger - Mateusz Okrutniak; Bartosz Rom; Filip Turza; Irena M. Grześ (Insects, 2020)
The association between the division of labour and worker body size of ants is typical for species that maintain physical castes. Some studies showed that this phenomenon can be also observed in the absence of distinct morphological subcastes among workers. However, the general and consistent patterns in the size-based division of labour in monomorphic ants are largely unidentified. In this study, we performed a field experiment to investigate the link between worker body size and the division of labour of the ant Lasius niger (Linnaeus, 1758), which displays limited worker size variation. We demonstrated that the body size of workers exploring tuna baits is slightly but significantly smaller than the size of workers located in the upper parts of the nest. Comparing the present results with existing studies, large workers do not seem to be dedicated to work outside the nest. We suggest that monomorphic workers of certain body sizes are flexible in the choice of task they perform, and food type may be the important determinant of this choice.